(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2025)
Background: The Double J (D-J) stent is commonly used following A-H pyeloplasty to facilitate the drainage of urine from the kidney to the bladder. One of the most frequent complications associated with the D-J stent is bacterial colonization, which can occur both on the stent itself and in the urine. However, bacterial colonization of an indwelling D-J stent may serve as a nidus for bacteriuria. The aim of this study was to identify the microbiological characteristics associated with stent colonization and urinary tract infection (UTI) in these patients, as well as to determine the drug susceptibility of the microorganisms involved. Methods: This study was conducted in the Department of Pediatric Surgery at Chittagong Medical College and Hospital over a period of twenty-four months, from January 2018 to December 2019. A total of 31 patients with unilateral PUJ obstruction who underwent A-H pyeloplasty were included in this study. D-J stents were placed and left in situ for four weeks. The main outcome variables were UTI, stent colonization, microorganisms cultured from both the D-J stent and urine, and their antibiotic sensitivities. Post-operative follow-ups were conducted at 2 weeks, 1 month, 3 months, 6 months, and 12 months following A-H pyeloplasty, utilizing urine routine microbiological examination (R/M/E) and culture and sensitivity (C/S) tests. Results: There was a total of 31 patients included in this study. The median age was 5 years (IQR: 1.7 years to 7 years), and the male-to-female ratio was 2.44:1. The affected side was right in 14 cases (45.2%) and left in 17 cases (54.8%). One month after the pyeloplasty, 41.9% of cases had positive urinary culture, and the proximal and distal segments of the D-J stent were colonized in 32% and 61.3% of patients, respectively. However, no statistically significant association was found between stent colonization and urine culture. The most commonly identified organisms colonized in both the stent and urine wereEscherichia coli. These cultured organisms were mostly sensitive to nitrofurantoin and meropenem. Conclusion: Bacterial colonization in the D-J stent does not always induce UTI. Escherichia coli was the most frequently identified organism found in both the stent and urine, while nitrofurantoin and meropenem demonstrated high sensitivity against this pathogen. Journal of Paediatric Surgeons of Bangladesh (2021) Vol. 12 (1 & 2):17-23